India and the Diasporic Imagination - Christian, Rita; Misrahi-Barak, Judith (Horizons anglophones, 2011)
The idea of India and the Indian diasporic imagination is the product of the rich scholarship being done on the Asian sub-continent, as well as in the many countries where South Asians have settled. The notion of 'many Indias' and many diasporas attempts to accommodate people with multiple identities, encompassing a complex amalgam that includes the bewildering diversity of the sub-continent and the challenging hybridity of the places where they have settled. The shaping and reshaping of identities are fundamental to the universal quest to belong and to create new homelands while not eliminating notions of the imagined ancestral homelands. The reality is, as this volume demonstrates, that old conceptions of India, even 'many Indias', are now inadequate to accommodate the fluid identities that characterize the Asian sub-continental diasporas.